ASBABUN NUZUL SEBAGAI ASAS DALAM MEMAHAMI AYAT AL-QUR’AN - Abdul Manaf (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2024)
The verses of the Qur'an, when examined in terms of their reasons for revelation, can be grouped into two categories. First, there are verses or surahs revealed without being associated with a specific reason. Second, there are verses or surahs revealed due to a background reason. Sometimes, these serve as responses to ongoing issues or answers to questions posed. The second category, though containing fewer verses, is extensively discussed in the field of Ulumul Qur'an. Understanding the asbabun nuzul (reasons for revelation) allows an individual to comprehend the substantial meaning of a verse – something that caused the revelation of a verse or several verses containing events or explaining their laws at the time of the occurrence of those events. On the contrary, one might misinterpret the messages of the Qur'an by neglecting the circumstances or situations that underlie them.